Film remakes as ritual and disguise. Film culture in transition. : from Carmen to Ripley / Anat Zanger. - Zanger, Anat
The first book-length account of the symbolic chains that link remakes and explain their disguises, Film Remakes as Rituals and Disguise is also the first book to explore how and why these stories are told. Anat Zanger focuses on contemporary retellings of three particular tales-Joan of Arc, Carmen, and Psycho-to reveal what she calls the remake's "rituals of disguise." Joan of Arc, Zanger demonstrates, later